ANALISIS POTENSI dan EFEKTIFITAS PAJAK DAERAH ATAS RUMAH KOS di KOTA MANADO - Simangunsong, Marsion Immanuel Kant; Saerang, David Paul Elia; Elim, Inggriani (GOING CONCERN : JURNAL RISET AKUNTANSI, 2015)
This regulation introduce the new system of taxation that is self assessment system occurred since 1984. This study determine how potential and realization of local taxes on boarding house toward original local income in Manado. This study explains potential and effectiveness of local tax toward boarding house in Manado. Whether the existing boarding house in Manado city and potentially effective for the implementation of local taxes imposed on the above 10 room boarding house. This study used a descriptive analysis method i9n which the research is done by collecting and analyzing the data collected and also explanation. This study concludes that the potential of the tax boarding house has great potential to be developed by the city of Manado especially department of regional income, where to impose a tax on the boarding house can increase regional real income of Manado in innovative way. To increase revenue from imposing tax of boarding house, is important to do socialization every three months to society who wants to open that business.